Kinetic freeze-out, particle spectra, and harmonic-flow coefficients from mode-by-mode hydrodynamics - Flörchinger, Stefan (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The kinetic freeze-out for the hydrodynamical description of relativistic heavy-ion collisions is discussed using a background-fluctuation splitting of the hydrodynamical fields. For a single event, the particle spectrum, or its logarithm, can be written as the sum of the background part that is symmetric with respect to azimuthal rotations and longitudinal boosts and a part containing the contribution of fluctuations or deviations from the background. Using a complete orthonormal basis to characterize the initial state allows one to write the double differential harmonic-flow coefficients determined by the two-particle correlation method as matrix expressions involving the initial fluid correlations. We discuss the use of these expressions for a mode-by-mode analysis of fluctuating initial conditions in heavy-ion collisions.
Gesehen am 27.11.2017